Authority figures : rhetoric and experience in John Locke's political thought - Shanks, Torrey (The Pennsylvania State University Press, 2014)
"Examines the place of rhetoric in John Locke's political and philosophical thought. Traces the close ties between rhetoric and experience as they form the basis for a theory and practice of judgment at the center of his work"--Provided by publisher.